Study on the Effect of Inoculation of Mixed Inoculation on Hydrolysis and Acidification Performance of Kitchen Waste - Huang, Yuanming; Yu, Songke; Hu, Jialun; Peng, Jinmei; Peng, Wei; Dong, Jianwei; Ning, Xinqing (International Journal of Natural Resources and Environmental Studies, 2024)
The effect of a mixture of different inoculants as inoculum on the hydrolytic and acidification process was investigated in order to improve the hydrolytic and acidification properties of kitchen waste. The results showed that the inoculation of Baijiu pit mud had the feasibility to improve the hydrolytic acidification performance during the hydrolytic acidification process of kitchen waste. At the end of the hydrolytic acidification process, the SCOD of the 1:0, 3:1,1:1, and 1;3 group increased by 55.97%, 48.67%, 30.82% and 7.03%, respectively, compared with that of the 1:0 group; the hydrolysis rate increased by 2.44%, 7.07%, 2.01% and 2.2% compared with that of the 0:1 group. The highest concentration of VFAs was found in the group with 1:3 ratio of Baijiu pit mud and anaerobic sludge, which was 11353.46 mg/L. The highest acidification rate was found in the 1:3 group, which was 68.57%, and 16.14% higher than that in the 1:0 group. The highest concentration of VFAs was found in the group with 1:3 ratio of Baijiu pit mud and anaerobic sludge, which was 11353.46 mg/L. The highest acidification rate was found in the 1:3 group, which was 68.57%, and 16.14% higher than that in the 1:0 group. Inoculation of Baijiu pit mud was able to change the fraction of VFAs during the hydrolytic acidification of kitchen waste. The fermentation type of the hydrolytic acidification system was ethanol-type fermentation, and the ethanol concentration was increased by 8.64, 8.59, 7.36, and 2.81 times in the groups with the ratio of Baijiu pit mud to anaerobic sludge of 1:0, 3:1, and 1:1, respectively. However, in the Baijiu pit mud and anaerobic sludge ratio of 1:3 and 0:1 group, the main type of fermentation was acetic acid type fermentation. The experimental groups inoculated with Baijiu pit mud.